LATAR CERITA DALAM NOVEL SENJA YANG TAK TERGANTIKAN KARYA RAHMA YUNIARSIH - Uli Wahyuni; Ronaldo Manullang (Universitas Batanghari, 2021)
The study analyzed the novel's literary work. This research aims to describe the story's background in the novel Senja Yang Tak Tergantikan by Rahma Yuniarsih. This research is included in qualitative descriptive analysis. The data are collected from quotations related to the background of the story, namely the background of the place, time, and social, then classified into a table of classification of data, which is then analyzed according to the basis of the theory. The data is analyzed using a structural approach. Based on the data analysis results, it is known that in the novel Senja Yang Tak Tergantikan By Rahma Yuniarsih, two hundred and forty-three quotations cover three aspects: one hundred fifty-seven place, thirty-nine-time background quotes, and forty-seven social background quotes. The results obtained from this study can be concluded that the story background quotes in the novel Senja Yang Tak Tergantikan By Rahma Yuniarsih more dominantly reveal the background of the place than the time and social background quotes contained in the novel Senja Yang Tak Tergantikan By Rahma Yuniarsih. Keywords: story background, novel, Senja yang Tak Tergantikan